2000
DOI: 10.1108/eum0000000005309
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability, growth and development

Abstract: The Brundtland Report (WCED, 1987) encouraged the view that the main threats to the environmental sustainability of development are poverty-driven depletion of environmental resources in the developing world, and consumption-driven pollution of the biosphere by the developed world. Recent work on the empirical relationship between per capita GDP growth and certain indicators of environmental quality seems to contradict this view. Some indicators of local air and water quality first worsen and then improve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…Wealthier countries have more to invest in pollution control, a stronger legal and administrative infrastructure, and more extensive technical and scientific resources than less-developed ones. In brief, at some stage of development citizens demand and government is able to deliver pollution control and conservation (Dasgupta et al 2006, p. 2;Dinda 2004;Perrings and Ansuategi 2000). One review of EKC studies concluded that ''regulation is the dominant factor in explaining the decline in pollution as countries grow beyond middle-income status.''…”
Section: Economic Growth and The Environmentmentioning
confidence: 97%
“…Wealthier countries have more to invest in pollution control, a stronger legal and administrative infrastructure, and more extensive technical and scientific resources than less-developed ones. In brief, at some stage of development citizens demand and government is able to deliver pollution control and conservation (Dasgupta et al 2006, p. 2;Dinda 2004;Perrings and Ansuategi 2000). One review of EKC studies concluded that ''regulation is the dominant factor in explaining the decline in pollution as countries grow beyond middle-income status.''…”
Section: Economic Growth and The Environmentmentioning
confidence: 97%
“…34. And if that argument has not been suf®ciently spelt out then it is a relatively simple matter to do so (see, e.g., Gray, 1992;Gray & Bebbington, 2000Bebbington & Thomson, 1996;Perrings & Ansuategi, 2000;Hawken et al, 1999;Weizsacker, 1997;Lamberton, 1998;Birkin, 1996;Milne, 1996). 35.…”
Section: Notesmentioning
confidence: 98%
“…Rich people have incentives to improve the environment to the extent that they themselves are affected by this degradation, but this is not the case when these effects move in time or space to other citizens (Arrow et al, 1995;Perrings, 2000). This is the case of global pollutants, such as CO 2 , for which there is an incentive to 'free ride'.…”
Section: Introduction: the Environmental Kuznets Curve Hypothesismentioning
confidence: 99%